Peran Pemerintah Desa Dalam Pengendalian Pengambilan Pasir Pantai Secara Ilegal Oleh masyarakat di Desa Air Kumpai, Kecamatan Suak Midai - Maya Gustiani Putri, Maya Gustiani Putri (Indonesian Journal Publisher, 2024)
Controlling illegal sand needs to be carried out in the hope of reducing the impact of damage to the environment and biological resources. This research aims to find out the role of the village. This research was conducted in Air Kumpai Village, Suak Midai District, Natuna Regency. The method used in this research is a qualitative method approach. Primary data collection was carried out by interviews with sources and respondents. Secondary data was obtained through literature study and documentation. The results of the research show that the Village government has attempted to control sand extraction in Air Kumpai Village. Efforts made by the government include conducting outreach and installing boards prohibiting sand extraction. Apart from that, there are still people who violate regulations and steal sand and do not understand the impact of damage to the environment or the necessities of life that encourage people to dare to steal sand. The village government and law enforcement officers are still less firm in taking action by criminal provisions regulated in statutory regulations.